Idiopatyczne zapalenie mięśnia zewnątrzgałkowego – opis przypadku - Gawęcki, Maciej; Bałasz-Duda, Beata (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
We present a case of idiopathic myositis of medial rectus muscle in 13-year old boy. Patient was admitted to pediatric ward due to severe headache and periorbital edema. In opthalmological examination serious limitation of adduction together with pain on the eye movements, was found. MRI of the orbit revealed significant enlargement of medial rectus muscle of the RE. Laboratory tests excluded thyroid dysfunction. Systemic steroid therapy was induced. Symptoms regressed 10 days after beginning of treatment.